Cutaneous lupus‐erythematosus‐like reaction arising after COVID‐19 vaccination. (4th August 2022) - Rose, Colin; Apgar, Ryan; Green, Margaret
Abstract: Multiple adverse cutaneous reactions have been described following vaccination against COVID‐19. This case report describes a reaction to the Pfizer‐BioNTech (BNT162b2) vaccine that histopathologically resembles cutaneous lupus erythematosus with vacuolar interface alteration, superficial to mid‐dermal perivascular and periadnexal lymphocytic infiltrate with clusters of CD123 + cells, and mildly increased dermal mucin.